NEUTRINOLESS DOUBLE-BETA DECAY IN AN SU(3)(L)CIRCLE-TIMES-U(1)(N) MODEL - PLEITEZ, V; Tonasse, M. D. (American Physical Soc, 1993)
We consider a model for the electroweak interactions with the SU(3)(L) circle times U(1)(N) gauge symmetry. We show that the conservation of the quantum number F = L+B forbids the appearance of massive neutrinos and the neutrinoless double-beta decay (beta beta)(0 nu). Explicit or/and spontaneous breaking of F implies that the neutrinos have an arbitrary mass. In addition the (beta beta)(0 nu) decay also has some channels that do not depend explicitly on the neutrino mass.